Navigating the Complexities of Body Image in Young Adults and Their Self-Acceptance - Manisha Khadga Yadav (Interdisciplinary Journal of Management and Social Sciences, 2025)
Body image encompasses individuals' perceptions and beliefs regarding their own physical appearance. It is shaped by personal and cultural factors and can manifest in either a positive or negative manner. Satisfaction with body image is associated with interpersonal success, happiness, healthier lifestyle, enhanced performance, and improved self-esteem. Dissatisfaction with body image stems from the gap between an individual's perceived and ideal physique. Factors such as media representations, social influences, and appearance-related ideal-type of teasing contribute to the development of negative body image, which can adversely affect both mental and physical health. The psychological construct of body image represents the underlying mental representation individuals possess regarding their bodies, shaping self-perception and their physical appearance. Individual perspectives on body image are expected to vary based on culture, race, age, education, profession, or social network; however, research reveals gender as the most significant factor. This paper presents the findings of primary research conducted with two dozen of young adults, who were interviewed regarding their satisfaction with their current body image and the underlying influencing factors. Body image satisfaction was found to be influenced by self-assessment of the body, health status, impression management, and other social factors. Participants' diverse perspectives underscore the complex interaction among social feedback and societal norms in shaping individual perceptions of beauty and attractiveness.